2020
DOI: 10.1371/journal.pone.0232359
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and effects of HIV-related stigma among youth living with HIV/AIDS in Western Uganda: A photovoice study

Abstract: HIV-related stigma has been identified as a significant stressor affecting Quality of Life of Youth Living With HIV/AIDS (YLWHA). Gaining a contextualized understanding of how this stigma is experienced by YLWHA in Western Uganda is crucial in addressing it in this group and setting. In this study, we explored the lived experiences of YLWHA with HIV-related stigma. Photovoice was used to gain insight into the lived experiences of HIV-related stigma in 11 YLWHA (15-19 years), purposively selected from a hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 62 publications
5
51
0
Order By: Relevance
“…The higher prevalence rates of opportunistic infections among adolescents with HIV possibly increase the risks of depression are reported in several prior studies [ 39 ]. The other potential reason is that adolescents with HIV are at greater risk to experience stigma, discrimination, social association, or marginalization when compared with the general population which is linked with a greater risk of depression among the exposed individuals [ 40 ]. The higher prevalence rates of mental disorders that possibly increasing the risk of depression among adolescents could be the other possible reason for the observed differences [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence rates of opportunistic infections among adolescents with HIV possibly increase the risks of depression are reported in several prior studies [ 39 ]. The other potential reason is that adolescents with HIV are at greater risk to experience stigma, discrimination, social association, or marginalization when compared with the general population which is linked with a greater risk of depression among the exposed individuals [ 40 ]. The higher prevalence rates of mental disorders that possibly increasing the risk of depression among adolescents could be the other possible reason for the observed differences [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the community readiness model [38], we hold that school communities by default need to be ready to receive and support YLWHA rather than instituting supportive measures following in-school disclosures. Since HIV is prevalent in this locality [6] and it is a highly stigmatized condition [18], schools should be at a high level of readiness regardless of any disclosures. Regrettably, our findings seem to place these schools at the level of vague awareness [39] in which they are concerned about the health issuesin this case care and support needs for YLWHA -but the motivation to address them is low.…”
Section: Discussionmentioning
confidence: 99%
“…Research on Ugandan secondary schools has shown that YLWHA are particularly vulnerable to HIV-related stigma, abuse, poor nutrition, mental and physical health difficulties, and poverty [6,[16][17][18][19][20][21]. Additionally, YLWHA often come from households that are economically challenged due to a high burden of healthcarerelated costs and loss of income due to ill or deceased adult members [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations